Activation of Primary and Secondary Benzylic and Tertiary Alkyl (sp3)C-F Bonds Inside a Self-Assembled Molecular Container - Köster, Jesper M.; Häussinger, Daniel; Tiefenbacher, Konrad (Frontiers in Chemistry, 2019)
Alkyl fluorides are generally regarded as chemically inert. However, several literature examples describe the activation of alkyl (sp3)C-F bonds via strong Brønsted or Lewis acids under harsh conditions. We here report that catalytic amounts of the self-assembled resorcinarene capsule are able to activate alkyl (sp3)C-F bonds under mild conditions (30 °C, no strong Brønsted or Lewis acid present). Kinetic measurements display a sigmoidal reaction progress after an initial induction period. Control experiments indicate that the accessible cavity of capsule is required for an efficient reaction acceleration.